PERANAN DAN SIKAP TRANSFORMASI POLITIK ULAMA DALAM MENGHADAPI PEMILU 2014 DI ACEH - Ridwan Hasan (Millah: Journal of Religious Studies, 2013)
Cleric is a person who always used various references in Acehnese society especially in politics today. Even now, most local political parties participated also pioneered by some scholars communities in Aceh. The role and attitude of the clergy in the face of the year 2014 election greatly affect the performance of legislative policy on the future, because the legislature is as representative of the general public. With the implementation of Qanun in Nanggroe Aceh Darussalam (NAD) policy concerning both national parties (Pamas) and local political parties (Parlok) has contributed and a more mature understanding of politics, because the phenomenon will occur in the 2014 election ahead is a form of democracy the general public. Surely democracy must apply the principle of the system or if only to push forward or succeed to be submitted a candidate, is one of the 2014 elections itself. So that all policies of public interest can be accepted and applied in different elements of the community through the election to be held.